2004
DOI: 10.1002/jsc.665
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence in leaders: an antidote for cynicism towards change?

Abstract: ᭹ Business leaders everywhere have encountered the reality of resistance and cynicism when introducing change initiatives. ᭹ This paper identifies some of the associations between the challenges of organizational change in the 21st century and the emotional competencies required of contemporary change leaders. ᭹ The aim of this paper is to explore the impact of leader emotional intelligence (EI) on levels of employee cynicism towards change. ᭹ Results from a survey of 448 employees supported the hypothesis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
0
28
0
2
Order By: Relevance
“…EI is also said to be a crucial factor in organization change [31,32], leadership (33,34,35,36], management performance [37], teachers' burnout level [38], university professors' self-efficacy [39] and life satisfaction [40].…”
Section: Emotional Intelligencementioning
confidence: 99%
“…EI is also said to be a crucial factor in organization change [31,32], leadership (33,34,35,36], management performance [37], teachers' burnout level [38], university professors' self-efficacy [39] and life satisfaction [40].…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Örgütsel sinizmin ortaya çıkmasında işgörenlerin kişilik yapısı, psikolojik sözleşme ihlali, liderlik davranışlarındaki eksiklikler (Çağ, 2011); çalışanlarda örgüt içerisinde adalet, namus, samimiyet, dürüstlük gibi prensiplerin kalmadığına dair oluşan inançlar (Naus, Iterso & Roe, 2007); diğerlerine karşı oluşan güvensizlik duygusu (Stanley, Meyer & Topolnytsky, 2005); alınan kararların samimiyetten uzak olması (Dean, Brandes & Dharwadkar, 1998); ve sürekli talep değişikliklerinden dolayı bireylerin iş ortamında hayal kırıklığı yaşamaları ve yorgun düşmeleri (Cartwright & Holmes, 2006) gibi nedenler etkili olmaktadır. Bu bağlamda örgüt performansının arttırılmasında birinci derecede sorumlu olan liderlerin mücadele etmek zorunda oldukları en önemli sorunlardan birisinin de örgütsel sinizm olduğu söylenebilir (Ferres & Connell, 2004).…”
Section: Introductionunclassified
“…Liderler değişim için adım atmak istedikleri her ortamda sinizmin getirdiği bir dirençle karşılaşmaktadırlar (Ferres & Connell, 2004). Eğer bireyler liderin kendilerini anlamadığını düşünmeye başlarlarsa (Reichers, Wanous & Austin, 1997) örgütsel sinizm eşliğinde örgütsel politikaları da yersiz ve yetersiz algılamaya başlarlar.…”
Section: Introductionunclassified
“…He suggests that organizations initiating change would benefit from appointing leaders who can establish [9.8.2011-11:49am] [1-28] K:/LEA/LEA 416890.3d (LEA) [PREPRINTER stage] productive emotional connections with their staff and from providing training and development programmes to enhance these abilities. Ferres and Connell (2004) found that followers' perceptions of high leader EI (using a mixed-model questionnaire) produced less cynicism about an organizational change. With reference to followers' emotions, Huy (2002) reports that middle managers in his study were expected to be task-oriented and not get emotionally involved.…”
Section: Leader Ei and Organizational Changementioning
confidence: 95%
“…Apparently only two studies have actually required followers to evaluate the EI of their leaders. In one, Ferres and Connell (2004), using a little known mixed-EI model, asked followers to rate the EI of their leaders. In the second, Lindebaum and Cartwright (2010), using Wong and Law's (2002) questionnaire, required leaders to rate their own EI while their line managers and two followers rated the EI and leadership style of the leaders.…”
Section: Ei and Leadershipmentioning
confidence: 99%